A novel CVaR-based conflict resolution model for optimal allocation of treated wastewater under bankruptcy conditions. (10th April 2020) - Tayebikhorami, Saeid; Nikoo, Mohammad Reza; Izady, Azizallah; Adamowski, Jan
Abstract: Increasing water resource demands associated with rapid population and industrial growth have raised important concerns regarding water supply under sustainable development. Some of these concerns have been alleviated by using treated wastewater (TWW) as an alternative water resource for applications such as irrigation and industrial cooling. To achieve optimal and equitable water resource allocation amongst stakeholders, a novel risk-based multi-objective TWW allocation optimization framework was developed to model stakeholders' conflicting objectives and to consider potential resource losses linked to uncertainty. The proposed framework was tested to determine the TWW allocation policy best suited to the eastern portion of the province of Tehran, Iran, for the planning horizon of 2031. The results indicate that first, the proposed model provides a reasonable sharing policy to effectively resolve conflicts between involved stakeholders. Second, the solutions are sensitive to the confidence level of the risk model during the optimization process, and hence, one has to be conservative in assigning a confidence value when using this framework. Third, the obtained compromise solution differs from the most preferred solution of each stakeholder, which is consistent with the nature of bargaining problems. Lastly, shortage occurred when trying to meet the demand of the municipal sector (MS), and therefore, bankruptcy procedures and social choice rules (SCR) were only applicable to the MS share of TWW. Results of SCRs revealed that the Constrained Equal Award method is preferred for the provision of a socially acceptable sharing scenario in the presence of a water shortage. Overall, the efficiency and efficacy of the developed equity-based model to resolve conflicts related to resource allocation were confirmed. Graphical abstract: Image 1 Highlights: A risk-based optimization model was used for treated wastewater allocation under uncertainty. A Conditional Value at Risk (CVaR) model was used to form the risk-based objective functions. A trade-off curve was obtained using the NSGA-II multi-objective optimization model. Unanimity fallback bargaining and social choice rules were used to select the compromise solution. Bankruptcy procedures were used to find equitable sharing scenarios in case of shortage.